Which policy of cooperation in matters of security and defence does Portugal need to adopt in Africa? - Bernardino, Luís Manuel Brás (2009)
Lusíada. Política internacional e segurança. - ISSN 1647-1342. - S. 1, n. 2 (2009). - p. 85-97.